Python Fundamentals a Practical Guide for Learning Python, Complete with Real-World Projects for You to Explore - Marvin, Ryan (Packt Publishing Ltd, 2018)
Python Fundamentals takes you from zero experience to a complete understanding of key concepts, edge cases, and using Python for real-world application development. You'll move progressively from the basics to working with larger complex applications. After completing this book, you'll have the skills you need to dive into an existing ...